Effect of eccentric action velocity on expression of genes related to myostatin signaling pathway in human skeletal muscle - Roschel, Hamilton; Ugrinowistch, Carlos; Santos, Audrei Reis; Barbosa, Wesley Pereira; Miyabara, Elen Haruka; Tricoli, Valmor; Aoki, Marcelo Saldanha (Biology of Sport, 2018)
The aim of this study was to investigate the effects of an acute bout of eccentric actions, performed at fast velocity (210º .s-1 ) and at slow velocity (20º .s-1 ), on the gene expression of regulatory components of the myostatin (MSTN) signalling pathway. Participants performed an acute bout of eccentric actions at either a slow or a fast velocity. Muscle biopsy samples were taken before, immediately after, and 2 h after the exercise bout. The gene expression of the components of the MSTN pathway was assessed by real-time PCR. No change was observed in MSTN, ACTRIIB, GASP-1 or FOXO-3a gene expression after either slow or fast eccentric actions (p > 0.05). However, the MSTN inhibitors follistatin (FST), FST-like-3 (FSTL3) and SMAD-7 were significantly increased 2 h after both eccentric actions (p 0.05). The current findings indicate that a bout of eccentric actions activates the expression of MSTN inhibitors. However, no difference was observed in MSTN inhibitors’ gene expression when comparing slow and fast eccentric actions. It is possible that the greater time under tension induced by slow eccentric (SE) actions might compensate the effect of the greater velocity of fast eccentric (FE) actions. Additional studies are required to address the effect of eccentric action (EA) velocities on the pathways related to muscle hypertrophy.